The role of memorable experience and emotional intelligence in senior customer loyalty to geriatric hotels - Prentice, Catherine (2022)
Drawing on service encounters and experiential marketing theories, this study examined the relationship between geriatric service, memorable experience, emotional intelligence, and senior customers' attitudinal and behavioural responses. The research was conducted at geriatric hotels in Portugal. The results showed that, compared to impersonal encounters, employee service has a significantly greater effect on customer satisfaction, memorable experience, and customer loyalty. In addition, customers' memorable experiences mediated the relationship between different service encounters and organisational outcomes. However, customers’ emotional intelligence had minimal effects on these relationships. The discussion and implications of these findings are offered to researchers and practitioners.